HLA-C-restricted viral epitopes are associated with an escape mechanism from KIR2DL2(+) NK cells in Lassa virus infection - Wauquier, Nadia (EBioMedicine, 2019)
BACKGROUND: Lassa virus (LASV) is the etiologic agent of an acute hemorrhagic fever endemic in West Africa. Natural killer (NK) cells control viral infections in part through the interaction between killer cell immunoglobulin-like receptors (KIRs) and their ligands. LASV infection is associated with defective immune responses, including inhibition of NK cell activity in the presence of MHC-class 1(+)-infected target cells. METHODS: We compared individual KIR and HLA-class 1 genotypes of 68 healthy volunteers to 51 patients infected with LASV in Sierra Leone, including 37 survivors and 14 fatalities. Next, potential HLA-C1, HLA-C2, and HLA-Bw4 binding epitopes were in silico screened among LASV nucleoprotein (NP) and envelope glycoprotein (GP). Selected 10-mer peptides were then tested in peptide-HLA stabilization, KIR binding and polyfunction assays. FINDINGS: LASV-infected patients were similar to healthy controls, except for the inhibitory KIR2DL2 gene. We found a specific increase in the HLA-C1:KIR2DL2 interaction in fatalities (10/11) as compared to survivors (12/19) and controls (19/29). We also identified that strong of NP and GP viral epitopes was only observed with HLA-C molecules, and associated with strong inhibition of degranulation in the presence of KIR2DL(+) NK cells. This inhibitory effect significantly increased in the presence of the vGP(420) variant, detected in 28.1% of LASV sequences. INTERPRETATION: Our finding suggests that presentation of specific LASV epitopes by HLA-C alleles to the inhibitory KIR2DL2 receptor on NK cells could potentially prevent the killing of infected cells and provides insights into the mechanisms by which LASV can escape NK-cell-mediated immune pressure.